Venezuela : Fiction in the Dark - Alvarado, Morella; Torrealba, Luisa (Obitel 2020: Melodrama in Times of Streaming, 2020)
During 2019, various situations once again showed the deep crisis in the country. Audiovisual production continued, albeit with figures that account for a declining industry. Four productions were released: a first was made by the state channel (TVe), a second by a local independent producer (Oduver Cubillán and BGcreativos), the third was produced by the private channel (RCTV) and broadcast by the subscription channel IVC Networks, and the fourth was also produced by RCTV. While the first two productions did not exceed the 35-episode figure, the third and fourth had 73 episodes. On March 7, there was the biggest blackout in the country’s history. For more than a week, 95% of the territory was paralyzed by a lack of electricity. The action was classified by the government as an electric sabotage. The darkness that covered the country also subsumed serial fiction.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Venezuela (corpus analysé); Venezuela (lieu de production du savoir); _Nettoyé

Uruguay: Ibero-American Fiction Loses Ground to Entertainment - Sánchez Vilela, Rosario; Gadea, Lucia (Obitel 2020: Melodrama in Times of Streaming, 2020)
A look at the screens of Uruguay’s open television in prime time will give the viewer a very reduced offer: after a television newscast that exceeds two hours long, there are only contest pro- grams, national or imported ones. It is possible that in the afternoon and at night the viewer finds a telenovela, almost always Turkish one. This is a very different panorama from the Uruguayan televi- sion history. Ibero-American fiction is in decline on open television, while its offer on VoD expands. In this chapter we will try to consider the various aspects of this landscape. Melodrama is on both options, open television and streaming, on a broad thematic spectrum, even in productions that are not usually classified as such. In the absence of national fiction in the period, at the end of the chapter we will study the melodrama in prison fiction, particularly in the case of El Marginal.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Uruguay (corpus analysé); Uruguay (lieu de production du savoir); _Nettoyé

Peru: Social Issues and Comedy in Fiction - Cassano, Giuliana; Vásquez, Guillermo; Dettleff, James A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
The country’s political crisis led to the confrontation between the Peruvian Congress and President Martín Vizcarra on irreconcil- able limits. After a second denial of confidence, Vizcarra made use of his constitutional prerogatives and dissolved Congress at the end of September 2019. The majority of the mass media step in line with the different positions of the Executive or the opposition, giv- ing much more attention to the political situation, thus modifying the TV programing. In this scenario, the Enfoca group – owner of Latina station – has continued looking for potential buyers, but without success yet. The conglomerate – with interest in financial, health and productive sectors – does not feel that the investment made in acquiring all the station’s shares seven years ago yielded the expected results. Meanwhile, Willax – a small locally held station acquired by the Wong group in 2015 with promises of a large investment – has become a stronghold of opposition to the government of Vizcarra and the largest broadcaster of Korean fictions. In February 2020, they an- nounced that a commercial partnership had been signed with South Korean company CJ ENM, a production company of several Korean dramas and the award-winning film Parasite, but without indicating what this company could mean for audiovisual production in Peru.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Pérou (corpus analysé); Pérou (lieu de production du savoir); _Nettoyé

Colombia: Melodrama Lives in Times of Streaming - Díaz, Fernando Aranguren; Bohórquez, Borys Bustamante; Riveros Solórzano, Hernán Javier (Obitel 2020: Melodrama in Times of Streaming, 2020)
The year 2019 in Colombia was characterized by the presence of a series of social and cultural phenomena of high impact on the population, such as the National Strike on November 21, when dif- ferent sectors expressed their disagreement with the country’s poli- cies and the reforms that were being proposed for the new year. This situation led to a leading presence of the news on the small screen and, at the same time, an interesting reflection of national identity, the needs of various Colombian social groups and the cul- tural matrices of the nation. In this hectic context and in accordance with a certain global climate of crisis in democratic and government systems, a highly interesting television phenomenon emerges: the highly successful reappearance of the programs that marked differ- ent generations of compatriots and that, as in the past, once again led families to discuss episodes and situations presented under the classical structure of melodrama.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); Colombie (corpus analysé); Colombie (lieu de production du savoir); _Nettoyé

Brazil: Time of Brazilian Streaming - Vassallo de Lopes, Maria Immacolata; Prezia Lemos, Ligia (Obitel 2020: Melodrama in Times of Streaming, 2020)
In 2019, the World Wide Web (www) celebrated its 30th anni- versary, However, the internet had not yet asserted itself as a right in the “network society” (Castells, 2009), and its balance points to the expansion of both opportunities and threats. Another fact that deserves to be highlighted in the year was the drop in the rating as a global phenomenon that challenges the television industry. It means change of habits and search for new business models. The integration of platforms and the generation of quality content appear as pillars of thetransformation of audiovisual worldwide. And the changes are manifested with a certain degree of diversity, according to the economic and cultural characteristics of each society, with disruptive processes.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé

Argentina: The Fall of Open TV Continues: Production Companies Bet on Platforms with Themes Regarding Marginality and Corruption - Aprea, Gustavo; Kirchheimer, Mónica S.; Rivero, Ezequiel A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
Serial fiction released in Argentina in 2019 continues to fall. Only one telenovela had more than 200 chapters. To a lesser extent than the previous year, the supply of serialized fiction incorporated themes from the social agenda, especially feminist struggles and the visibility of sexual dissidence. The channels found in the co-produc- tion and in the production for platforms one of the ways in which fic- tion survives. Some of these programs are now on the open television screen. New fiction releases from Ibero-America are also falling.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Argentine (corpus analysé); Argentine (lieu de production du savoir); _Nettoyé